Rethinking the implementation of the revised history curriculum: challenges faced by teachers, learners and principals in selected public secondary schools in Khomas region, Namibia - Mothowanaga, Ndinelao N.; Gladwin, Bhebhe (Namibian Journal for Research, Science and Technology, 2022)
The purpose for this study was to rethink the implementation of revised History curriculum in Namibia focusing on the Khomas regions, Windhoek. In line with qualitative research the study adopted an interpretivism paradigm, qualitative approach and case study research design. The targeted population consisted of school principals, history teachers and learners in three selected schools in Immanuel Shifidi cluster. Purposeful sampling technique was used to select teachers with three and more years of experience as history teachers. Cluster sampling was used to select learners from School A, B & C. Face to face interviews, non-participant observation and document analysis were used as data collection methods and thematic analysis was used to analyse data collected using these instruments. The study revealed that training and workshops were conducted on the implementation of revised history curriculum but the majority of participants did not attend the in-service training and workshop because only few teachers were selected to be part of the training. The study also revealed that some teachers lacked knowledge in some history topics and concepts which affected the implementation of the curriculum. The challenges faced in the implementation of the revised curriculum were overcrowded in classrooms, lack of textbooks, inadequate resources such as libraries, lack of government funds and lack of time management. The study recommended teachers should make an effort to collaborate with other history teachers in the Immanuel Shifidi circuit. The collaboration forums are intended to aid them in sharing subject knowledge and assisting one another in teaching diverse historical themes and topics. The school administration should seek funding from various companies in Namibia to help create libraries, purchase textbooks for students, and purchase classroom desks. NIED should hold regular training and workshops in various circuits and have a followup system in place to ensure that the trainings are effective. This will aid teachers in understanding the varied expectations of the new curriculum as well as staying current on curricular revisions. The study further recommends that future researchers should focus on training topics that need to be covered during curriculum in-service trainings and workshops for efficient delivery of revised history curriculum.